Long‐Term Systemic Inflammation and Cognitive Impairment in a Population‐Based Cohort. Issue 9 (14th August 2014) - Wichmann, Margarete A.; Cruickshanks, Karen J.; Carlsson, Cynthia M.; Chappell, Rick; Fischer, Mary E.; Klein, Barbara E. K.; Klein, Ronald; Tsai, Michael Y.; Schubert, Carla R.
<x xml:space="preserve">Abstract</x> Objectives Evidence suggests inflammation is associated with cognitive impairment, but previous epidemiological studies have reported conflicting results. Design Prospective population‐based cohort. Setting Epidemiology of Hearing Loss Study participants. Participants Individuals without cognitive impairment in 1998–2000 (N = 2, 422; 1, 947 with necessary data). Measurements Cognitive impairment (Mini‐Mental State Examination score <24 or diagnosis of dementia) was ascertained in 1998–2000, 2003–2005, and 2009–2010. Serum C‐reactive protein (CRP) and interleukin‐6 (IL‐6) were measured in 1988–1990, 1998–2000, and 2009–2010; tumor necrosis factor‐alpha was measured from 1998–2000. Results Participants with high CRP in 1988–1990 and 1998–2000 had lower risk of cognitive impairment than those with low CRP at both time points (hazard ratio (HR) = 0.46, 95% confidence interval (CI) = 0.26–0.80). Risk did not differ according to 10‐year IL‐6 profile or baseline inflammation category in the whole cohort. In sensitivity analyses restricted to statin nonusers, those with high IL‐6 at both times had greater risk of cognitive impairment than those with low IL‐6 at both times (HR = 3.35, 95% CI = 1.09–10.30). In secondary analyses, each doubling of IL‐6 change over 20 years was associated with greater odds of cognitive impairment in 2009–2010 in the whole cohort (odds ratio (OR) = 1.40, 95% CI = 1.04–1.89), whereas a doubling of CRP change over 20 years was associated with cognitive impairment only in statin nonusers (OR = 1.32, 95% CI = 1.06–1.65). Conclusion With data collected over 20 years, this study demonstrated greater likelihood of cognitive impairment in individuals with repeated high or increasing IL‐6. The inconsistent CRP findings may reflect effects of statin medications, survival effects, or adverse effects associated with chronically low CRP. Further studies of long‐term inflammation and cognitive impairment are needed.